Damage detection and quantification using thin film of ITO nanocomposites - Takiuti, Breno Ebinuma [UNESP]; Júnior, Vicente Lopes [UNESP]; Brennan, Michael J. [UNESP]; Arlindo, Elen Poliani S. [UNESP]; Orlandi, Marcelo Ornaghi [UNESP] (My University, 2014)
Many techniques for structural health monitoring (SHM) have been studied with the objective of ensuring the structural integrity of aeronautical structures. One of the most recent solutions for this problem is the use of continuous sensors, constituted by thin films made of nanocomposites. Since the nanocomposites, as any other composite material, can be tailored according to the application needs, there is a vast range of material that has the properties needed to detect damage. The work in this paper proposes the use of a new kind of sensor with nanowires or nanobelts of ITO (indium tin oxide) inserted in a polymeric matrix, such as PMMA (poly(methyl methacrylate) or acrylic). PMMA is transparent and it gives a very nice appearance to the monitored surface. In order to evaluate the effectiveness of this method, several tests are proposed. These tests consist of monitoring the behavior of the nanocomposites when affected by some kind of damage, which can be a mass addition, excessive strains or a crack. The resistivity of the nanocomposite was measured using a two point conventional conductivity test and showed promising results, where the sensors form a net, similar to a neural network capable of sensing structural variations.
Keywords: Continuous sensors; ITO; Nanocomposite; Neural network; Structural health monitoring